Accounting Errors and Errors of Accounting - Christensen, John (The Accounting Review, 2010)
ABSTRACT: Accounting should pay more attention to errors, as errors are essential for the updating of beliefs. Accounting is an information system, and errors are the carriers of information according to Bayes’ Theorem. Accountants are primarily concerned with the mean (value), but the variance of accounting numbers is equally important. Only autocorrelation makes historical accounting relevant for decision purposes. Endogenous errors of accounting are more common than acknowledged. First, the accounting model is linear, whereas the world is nonlinear. Second, accounting is not the only information channel, and accountants must consider the role of accounting when it supplements other information sources. This commentary discusses the consequences of endogenous errors. Errors are inherent to accounting, and accountants must address them.